1988
DOI: 10.1111/j.1600-0722.1988.tb01585.x
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion current and pH rise around titanium coupled to dental alloys

Abstract: Ra%'nholt G: Corrosion current and pH rise around titanium coupled to dental alloys. Scand J Dent Res 1988: 96: 466-72. Abstract -Corrosion reactions around titanium, usually considered biologically inert, might be provoked by coupling it galvanically with more eorrodible dental alloys. Experiments in vitro simulating tbe conditions of a titanium dental implant or root canal post coupled to an amalgam filling, demonstrated corrosion current densities up to 31 nA/cm', anodic pH values around the amalgam dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 13 publications
2
30
0
3
Order By: Relevance
“…But some of the dental implant components like abutment, abutment screws, and various attachments are made of gold alloys, Co-Cr alloys and stainless steels. [14] Titanium is the material of choice for intraosseous applications because it has typical properties like high passivity, resistance to chemical dose. Also, it has ability to repair itself if damaged.…”
Section: Metals and Ceramicsmentioning
confidence: 99%
“…But some of the dental implant components like abutment, abutment screws, and various attachments are made of gold alloys, Co-Cr alloys and stainless steels. [14] Titanium is the material of choice for intraosseous applications because it has typical properties like high passivity, resistance to chemical dose. Also, it has ability to repair itself if damaged.…”
Section: Metals and Ceramicsmentioning
confidence: 99%
“…Generally, the γ 2 phase dissolves following eq. (11): 11) 8Sn 7 Hg + 21O 2 + 42H 2 O + 28Cl − → 14Sn 4 (OH) 6 Cl 2 + 8Hg (11) This reaction indicates that the tin ions released from the γ 2 phase formed a complex salt with oxygen and chlorine and that mercury contained in the γ 2 phase formed mercury metal. Though part of the mercury metal changes to oxides and chlorides, the rest evaporates.…”
Section: Decrease Of Released Ionsmentioning
confidence: 99%
“…6) Ravnholt 7) measured galvanic current densities between amalgams and titanium in 1 mass% sodium chloride solution and showed that the conventional and the high-copper amalgams preferentially corroded as anodes compared to titanium as a cathode. Johansson and Bergmanet 8) measured the galvanic current densities of amalgams in contact with titanium in 0.9 mass% sodium chloride solution and reported that the galvanic current was always anodic on the conventional amalgam.…”
Section: )mentioning
confidence: 99%
“…A post and core assembly with unlike metals poses a potential for corrosion due to generation of a galvanic current (Pameijer, Glantz & Mobasherat, 1983;Ravnholt, 1988;Fernandes & Dessai, 2001). Non-noble metals, such as stainless steel, can promote corrosion or be subject to corrosion in non-biologic (Pickering, Beck & Fontana, 1962;McNally, 2004) and in biologic environments such as in the mouth (Silness, Gustavsen & Hunsbeth, 1979;Pameijer & others, 1983;Beague, 1992;Luu & Walker, 1992;Angell, 1999;Beech & Gaylarde, 1999;Kusy & others, 2002).…”
Section: Introduction and Purposementioning
confidence: 99%
“…The research by Pickering and others (1962) and Hoke and others (1983) demonstrated stress forces and/or the wedging effect of metal corrosion in confined spaces. To avoid encouraging corrosion, it has been recommended that metals of differing electrochemical potential not be mixed, and that noble metal posts and cores made of the same metal be used (AngmarMånsson & others, 1969;Arvidson & Wróblewski, 1978;Ravnholt, 1988;Luu & Walker, 1992).…”
Section: Introduction and Purposementioning
confidence: 99%